The Influence of Internal Control, Competence of Village Apparatus, and Compliance with Accounting Rules on Fraud Prevention in Village Fund Management - Sayang, Sabulon; Reo, Hermanus; Padhi, Siprianus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This research aims to determine the influence of internal control, village apparatus competence, and compliance with accounting rules on preventing fraud in managing village funds in Ende Regency. In this research, data was obtained by distributing questionnaires to 40 respondents to village officials throughout Ndori District, Ende Regency. The data obtained were analyzed using descriptive analysis and multiple regression. The research variables consist of an independent variable (X) and a dependent variable (Y). Independent variables include internal control, village apparatus competency, and compliance with accounting rules. Meanwhile, the dependent variable is fraud prevention. The results of this study indicate that internal control, competence of village apparatus, and observance of accounting rules have an effect on fraud prevention either partially or simultaneously.